Orthogonal frequency division multiple access fundamentals and applications - Jiang, Tao , 1970 Jan. 8-; Song, Lingyang; Zhang, Yan , 1977- (Wireless networks and mobile communications, 2010)
Provides an introduction to the foundations, applications, and design issues in OFDMA networks. This book explores key techniques of effective resource management, highlighting open problems and supplying possible solutions. It is suitable for those who work in fields related to OFDMA application or other multiuser communication system projects